Ionospheric Alfvén resonator control over the frequency-variable Pc1 event in Finland on May 14, 1997 - Prikner, K; Mursula, K; Kangas, J; Feygin, F. Z
The ionospheric Alfvén resonator (IAR) control mechanism over the EMIC wave transmission to the ground is demonstrated on a selected long-term frequency-variable subauroral Pcl event. The proper ionospheric plasma data obtained from EISCAT were accessible in a wide altitude range. Applying the numerical method of simulation of a realistic inhomogeneous IAR, the problem of appearance and disappearance of the ground Pc1 signal record was clarified on the basis of coincidence between the EMIC wave frequency spectrum and the IAR fundamental frequency peak (the frequency window). A shift of the signal source field line to lower latitudes during the development of the disturbance was noticed, and the signal frequency variation on the ground was modelled in the nonstationary IAR. Variation of the IAR altitude structure in the fundamental frequency was illustrated on altitude profiles of the normalized wave magnetic field amplitude in the horizontal and vertical components. Particular conditions of L‖- and R‖-wave mode incidence were assumed. The electron density vertical profile of IAR determines the effective resonator dimensions. In this way the IAR fundamental frequency window controls the signal within the ionosphere and on the ground. K. Prikner, K. Mursula, J. Kangas, F. Z. Feygin. Obsahuje bibliografii